2007
DOI: 10.1111/j.1439-0418.2006.01116.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of intercropping different cereal species in controlling lepidopteran stemborers on maize in Kenya

Abstract: The effects of mixed cropping systems containing maize, sorghum, millet and beans on infestations of cereals by lepidopteran stemborers and on associated parasitoids, as well as on yields and land equivalent ratios (LER) were assessed during four consecutive rainy seasons at two sites in the semi-arid eastern region of Kenya. Systems containing the non-host bean were more efficient in reducing pest densities than those with millet or sorghum only. Higher parasitism in diversified systems compared to monocrops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 41 publications
5
26
0
2
Order By: Relevance
“…On the other hand, intercropping with aromatic plants not only provides alternate habitats but also provides alternate food or intermediate hosts for predators, thus increasing natural enemies' population in an intercropped system [35,36]. Based on the current study's results, combined use of agronet cover and companion planting helped to lower B. tabaci infestation of tomatoes.…”
Section: Discussionmentioning
confidence: 58%
“…On the other hand, intercropping with aromatic plants not only provides alternate habitats but also provides alternate food or intermediate hosts for predators, thus increasing natural enemies' population in an intercropped system [35,36]. Based on the current study's results, combined use of agronet cover and companion planting helped to lower B. tabaci infestation of tomatoes.…”
Section: Discussionmentioning
confidence: 58%
“…The majority of cereal/legumes intercropping systems are widespread in Africa (Ndakidemi 2006) and India (Ghosh et al 2007), and thoroughly studied in details. Songa et al (2007) found that maize/bean systems had LER values >1.65 while some other intercropping with several cereal species including sorghum, and millet, gave LER values <1.…”
Section: Yield Advantage and Land-use Efficiencymentioning
confidence: 99%
“…Higher yields have been reported when competition between the two species of intercrop (maize + soybean) was lower than competition with the same species (Vandermeer, 1989). Agyar et al, (2006) and Songa et al (2007) observed intra and inter specific competition in many combinations of several crops (maize, sorghum, millet, cassava and bean). So the maize grain yield produced in the combination maize + bean was higher than in the combination maize+sorghum, while the combination maize +millet showed the lowest grain yield.…”
mentioning
confidence: 97%